From a shared origin to divergent frames: A computational analysis of media representations of Kampo Medicine and Traditional Chinese Medicine in Asahi Shimbun - Xi Chen; Jieqiong Wang; Xinying Liu (PLoS ONE, 2026)
Based on a corpus of news articles published in Asahi Shimbun over four decades (1984–2025), this study examines how Kampo medicine and Traditional Chinese Medicine (TCM), two medical traditions sharing a common historical origin, are discursively represented in Japanese mainstream media. Using topic modeling and word embedding analysis, it analyzes long-term patterns at two levels: thematic structures identified through topic modeling and semantic associations derived from word embeddings. The results show that Asahi Shimbun consistently differentiates Kampo medicine and TCM through sustained thematic and semantic organization. At the thematic level, coverage is structured across six domains, within which Kampo medicine is more stably integrated into core public concerns related to health practices and material supply, while TCM is more often situated in culturally oriented, comparative, or externally referenced contexts. Diachronically, these distinctions persist while adjusting to changing social demands and policy priorities. At the semantic level, Kampo medicine and TCM form distinct and relatively stable semantic neighborhoods. Kampo medicine is closely associated with concrete therapeutic entities, while TCM is framed within abstract classificatory, institutional, and system-oriented concepts. Together, thematic differentiation and semantic stabilization reinforce a clear discursive boundary between the two traditions. These findings reveal how Japanese mainstream media differentially position homologous medical knowledge over the long term, highlighting their role in shaping meaning within the modern nation-state context. The study applies recontextualization to long-term media analysis and shows how agenda-setting and framing contribute to the localization and othering of homologous knowledge. By linking macro-level thematic structures with micro-level semantic patterns, it further clarifies how media discourse shapes knowledge boundaries and cultural identity, extending the application of recontextualization theory in health and cross-cultural communication research.